Scientific writing considerations: introduction and methods - Castro-Rodríguez, Yuri (2018)
Scientific writing involves the knowledge of the rules and protocols related with argumentation, explanation, spelling, style and text editing. Writing and reading scientific papers are key skills for researchers. Classically, original articles present as a general structure: introduction, methods, results and discussion (IMRaD). All topics present their own characteristics and writing standards that are assessed by the editors and reviewers; these assessments will decide the acceptance or rejection of a manuscript for publication in a scientific journal. This scientific note summarizes some suggestions for properly writing an introduction and the methods of a scientific article.